MUSCULAR ABNORMALITIES IN SUBMENTAL TRIANGLE – VARIATIONS OF ANTERIOR BELLY OF DIGASTRIC MUSCLE - S. Novakov; S. Delchev (Trakia Journal of Sciences)
The aim of this study is to highlight some unusual morphology of the digastric muscle anterior belly. During dissection of the bodies used in the practical lessons for second year medical students we found abnormal pattern of the suprahyoid region in the necks of two adult male cadavers. Both were with variable anterior bellies of digastric muscles. Case 1 presented a unilateral left variation, with an anomalous anterior belly. Case 2 presented bilateral variation, with the presence of two supernumerary bellies. Though multiplicity of anterior belly is common we provide interesting variations with anatomical and clinical importance. The different variants of the anterior belly of the digastric muscle can be found during the routine dissection or surgical procedure or imaging techniques. Anatomical variations of the anterior bellies of the digastric muscles can be easily confused with pathological conditions in CT and MR imaging. It is necessary to recognize that variants of the digastric muscle may happen in order to escape confusion when diagnosing abnormal lesions of the floor of the mouth and submental region.